A novel gene of Kalanchoe daigremontiana confers plant drought resistance - Wang, Li (Sci Rep, 2018)
Kalanchoe (K.) daigremontiana is important for studying asexual reproduction under different environmental conditions. Here, we describe a novel KdNOVEL41 (KdN41) gene that may confer drought resistance and could thereby affect K. daigremontiana development. The detected subcellular localization of a KdN41/Yellow Fluorescent Protein (YFP) fusion protein was in the nucleus and cell membrane. Drought, salt, and heat stress treatment in tobacco plants containing the KdN41 gene promoter driving β-glucuronidase (GUS) gene transcription revealed that only drought stress triggered strong GUS staining in the vascular tissues. Overexpression (OE) of the KdN41 gene conferred improved drought resistance in tobacco plants compared to wild-type and transformed with empty vector plants by inducing higher antioxidant enzyme activities, decreasing cell membrane damage, increasing abscisic acid (ABA) content, causing reinforced drought resistance related gene expression profiles. The 3,3′-diaminobenzidine (DAB) and nitroblue tetrazolium (NBT) staining results also showed less relative oxygen species (ROS) content in KdN41-overexpressing tobacco leaf during drought stress. Surprisingly, by re-watering after drought stress, KdN41-overexpressing tobacco showed earlier flowering. Overall, the KdN41 gene plays roles in ROS scavenging and osmotic damage reduction to improve tobacco drought resistance, which may increase our understanding of the molecular network involved in developmental manipulation under drought stress in K. daigremontiana.